Pengembangan Website E-Commerce dan Sistem Informasi Untuk Penjualan Produk The Hidden Swargi Coffe Roaster - Tina Anjarwati; Heru Supriyano (LPPJPHKI Universitas Dehasen Bengkulu, 2026)
This study discusses the development of an e-commerce website integrated with the information system at The Hidden Swargi Coffee Roaster. The background of this study stems from the need for businesses to improve operational efficiency while expanding their marketing reach in the digital age. The method used in the development is the Waterfall model, which includes the stages of requirements analysis, system design, implementation, and testing. The results of the study show that the system built is capable of supporting product management, transactions, and customer data in a more structured and integrated manner. Testing using the Black Box method proves that all functions in the system run according to the design and user requirements. With this system, The Hidden Swargi Coffee Roaster can strengthen its business processes while improving the quality of service to customers. This research is expected to provide practical contributions to MSMEs in the application of information technology and serve as an academic reference in the development of integrated e-commerce systems.